Forensic characteristics and phylogenetic analysis of 23 Y-STR loci in the Miao population from Guizhou province, southwest China - Pengyu Chen; Guanglin He; Hao Xing; Hongyan Gao; Menge Wang; Min Zhao; Li Luo; Jian Wu; Jian Yu; Yanyan Han (Annals of Human Biology, 2019)
Background: Investigation of haplotype/allele frequency data of Y-STR loci in ethnically diverse populations is essential for forensic reference database construction and genetic application. However, the population genetic characteristics of the Chinese Miao minority from Guizhou Province remain uncharacterised. Aim: To assess forensic characteristics for 23 Y-Chromosomal STR loci in Guizhou Miao and explore population genetic relationships with geographically neighbouring populations. Subjects and methods: Twenty-three Y-Chromosomal STRs were genotyped using the Powerplex® Y23 system in 103 unrelated Chinese Miao males from Guizhou Province, southwest China. Haplotypes and forensic parameters were obtained. Population relationships of Guizhou Miao with others were revealed using AMOVA and an MDS plot. Results: A total of 96 haplotypes were identified with overall haplotype diversity (HD) and discrimination capacity (DC) of 0.9985 and 0.9320, respectively. Genetic differentiation was observed with most of the comparison populations, prominently for Guizhou Shui. Conclusion: The 23 Y-STR loci were highly polymorphic and discriminating in the Guizhou Miao population and could be used for forensic practice and population genetic studies. Population relationship analysis revealed Guizhou Miao had a close genetic relationship with geographically close Guizhou Gelao, as well as Han majorities derived from different regions.